Wastewater characterisation by combining size fractionation, chemical composition and biodegradability - Ravndal, Kristin T.; Opsahl, Eystein; Bagi, Andrea; Kommedal, Roald (Elsevier, 2017)
The potential for resource recovery from wastewater can be evaluated based on a detailed characterisation of wastewater. In this paper, results from fractionation and characterisation of two distinct wastewaters are reported. Using tangential flow filtration, the wastewater was fractionated into 10 size fractions ranging from 1 kDa to 1 mm, wherein the chemical composition and biodegradability were determined. Carbohydrates were dominant in particulate size fractions larger than 100 μm, indicating a potential of cellulose recovery from these fractions. While the particulate size fractions between 0.65 and 100 μm show a potential as a source for biofuel production due to an abundance of saturated C16 and C18 lipids. Both wastewaters were dominated by particulate (>0.65 μm), and oligo- and monomeric (<1 kDa) COD. Polymeric (1–1000 kDa) and colloidal (1000 kDa-0.65 μm) fractions had a low COD content, expected due to degradation in the sewer system upstream of the wastewater treatment plant. Biodegradation rates of particulate fractions increase with decreasing size. However, this was not seen in polymeric fractions where degradation rate was governed by chemical composition. Analytical validation of molecular weight and particle size distribution showed below filter cut-off retention of particles and polymers close to nominal cut-off, shifting the actual size distribution.
Keywords: Wastewater fractionation; Wastewater characterisation; Resource recovery; Biodegradability